We built this city - London, Matt, (London, Matt. 8th continent ;, 2016)
Rick and Evie Lane have finally built their dream city on the 8th continent. But the Lanes soon find out that Mastercorp doesn't give up quite so easily. The totally terrifying corporation has a few nasty tricks up its top-secret sleeves, including a weapon with astonishing powers -- and eight tentacles. Now it's Lanes vs. Mastercorp in an all-out war that will take Rick and Evie from the murkiest depths of the ocean to the steamiest parts of the jungle. With evil Mastercorp agents, animal cyborgs, and a robot bully on their tails, rick and Evie must find a way to save the city -- and the home -- that they've built together. -- Publisher's description.